2012
DOI: 10.11113/jt.v48.235
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Breakage During Roller Milling of Wheat Kernels, Based on Single Kernel Measurements

Abstract: Pengilangan tepung gandum melibatkan pengisaran bijirin secara berulang-kali (menggunakan roller mill) dan pemisahan (secara pengayakan) bagi perolehan semula hasilan tepung yang berkesan yang secara bandingannya bersih dari pencemaran bran. Satu permulaan bagi membina model perlakuan terhadap campuran bijirin gandum ialah keupayaan bagi menentu-ukur kelainan ciri-ciri yang wujud dalam campuran tersebut. Alatan Perten Single Kernel Characterisation System (SKCS) dapat memberikan taburan kuantitatif bagi jisim,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Beside of this the SKCS measures the weight, diameter, and moisture of (usually) 300 individual kernels within 5 min, and provides information in the form of means and distributions (Muhamad and Campbell 2004). The numerous workers have applied the SKCS to a range of studies and have concluded that it gives useful results, especially for prediction wheat milling performance (Osborne et al 1997;Muhamad et al 2008). However there are no studies concerning the relation between SKCS parameters and impact grinding results, especially in relation to wholemeal flour production.…”
Section: Introductionmentioning
confidence: 99%
“…Beside of this the SKCS measures the weight, diameter, and moisture of (usually) 300 individual kernels within 5 min, and provides information in the form of means and distributions (Muhamad and Campbell 2004). The numerous workers have applied the SKCS to a range of studies and have concluded that it gives useful results, especially for prediction wheat milling performance (Osborne et al 1997;Muhamad et al 2008). However there are no studies concerning the relation between SKCS parameters and impact grinding results, especially in relation to wholemeal flour production.…”
Section: Introductionmentioning
confidence: 99%